(untitled) (British Journal of Global Ecology and Sustainable Development, 2023)
It is useful to provide robots with automation system capabilities in technological system processes. These robots allow technological processes to be carried out correctly and avoiding the intervention of human operators, which can be economically beneficial and security conditions are discussed in the article. In automation, most cases require the use of path planners that run the robot and one can think about how to move from one place to another at the same time. From their search parameters can be the most appropriate path planning algorithm according to the requirements set by the users and given the large number of approaches available in the literature, a difficult situation can arise. Besides, the past reviews analyzed here cover only some of these approaches, missing important ones. Therefore, our article aims to serve as a starting point for a clear and comprehensive review the research carried out to date is reflected. It presents a global classification of path planning algorithms with a focus on and on these approaches, which are used alongside autonomous ground vehicles, but can be extended to others we will be able to use the system scheme of robots that move on surfaces like autonomous boats. Also, the models used to illustrate along with the mobility and dynamics of the robot, the environment is also considered in perspective need to switch to road planning technology software. Each of the road planning categories specified in the classification shall be disclosed and is analyzed. At the end of technological processes, discussions about their application are given.